Answer: -1/2x - 2.
Step-by-step explanation:
To find the quadratic function y = a(x-h) that passes through the points (6, -1) and (4, 0), we can substitute the given points into the equation and solve for a and h. Let's go through the steps:
1. Substitute the coordinates of the first point (6, -1) into the equation:
-1 = a(6 - h)
2. Substitute the coordinates of the second point (4, 0) into the equation:
0 = a(4 - h)
3. Now we have a system of two equations with two unknowns. We can solve this system to find the values of a and h.
From the equation -1 = a(6 - h), we can rewrite it as:
-a(6 - h) = 1
From the equation 0 = a(4 - h), we can rewrite it as:
-a(4 - h) = 0
4. Simplifying the equations, we get:
-6a + ah = 1 (equation 1)
-4a + ah = 0 (equation 2)
5. Subtracting equation 2 from equation 1 eliminates the ah term:
-6a + ah - (-4a + ah) = 1 - 0
-6a + ah + 4a - ah = 1
-2a = 1
6. Solving for a, we divide both sides by -2:
a = -1/2
7. Substitute the value of a back into either equation (let's use equation 2) to solve for h:
-4(-1/2) + h(-1/2) = 0
2 + h/2 = 0
h/2 = -2
h = -4
8. Now we have the values of a = -1/2 and h = -4. We can substitute these values back into the original equation y = a(x-h) to find the quadratic function:
y = -1/2(x - (-4))
y = -1/2(x + 4)
y = -1/2x - 2
Therefore, the quadratic function that passes through the points (6, -1) and (4, 0) is
AI-generated answer
To find the quadratic function y = a(x-h) that passes through the points (6, -1) and (4, 0), we can substitute the given points into the equation and solve for a and h. Let's go through the steps:
1. Substitute the coordinates of the first point (6, -1) into the equation:
-1 = a(6 - h)
2. Substitute the coordinates of the second point (4, 0) into the equation:
0 = a(4 - h)
3. Now we have a system of two equations with two unknowns. We can solve this system to find the values of a and h.
From the equation -1 = a(6 - h), we can rewrite it as:
-a(6 - h) = 1
From the equation 0 = a(4 - h), we can rewrite it as:
-a(4 - h) = 0
4. Simplifying the equations, we get:
-6a + ah = 1 (equation 1)
-4a + ah = 0 (equation 2)
5. Subtracting equation 2 from equation 1 eliminates the ah term:
-6a + ah - (-4a + ah) = 1 - 0
-6a + ah + 4a - ah = 1
-2a = 1
6. Solving for a, we divide both sides by -2:
a = -1/2
7. Substitute the value of a back into either equation (let's use equation 2) to solve for h:
-4(-1/2) + h(-1/2) = 0
2 + h/2 = 0
h/2 = -2
h = -4
8. Now we have the values of a = -1/2 and h = -4. We can substitute these values back into the original equation y = a(x-h) to find the quadratic function:
y = -1/2(x - (-4))
y = -1/2(x + 4)
y = -1/2x - 2
Therefore, the quadratic function that passes through the points (6, -1) and (4, 0) is y = -1/2x - 2.
Answer:
(-2, 12)
Step-by-step explanation:
Answer:
b
d
Step-by-step explanation:
1 gallon = 8 pint
3 x 8 = 24 pints
the first option is wrong
1 quart = 4 cups
5 x 4 = 20 cups
the second option is correct
1 gallon = 4 quarts
6 x 4 = 24
the third option is wrong
1 pint = 16 ounces
2 x 16 = 32 ounces
the fourth option is correct
1 pint = 2 cups
8 x 2 = 16 cups
the fifth option is wrong
Answer:
B
Step-by-step explanation:
Answer:
wheres the rest of the graphs?
Step-by-step explanation:
It’s NOT the first one
Answer:
75
Step-by-step explanation:
Answer:
27cm²
Step-by-step explanation:
it should be the area of rectangle..
Answer:
Step-by-step explanation:
27 sq cm